2019
DOI: 10.1007/s00294-019-01006-5
|View full text |Cite
|
Sign up to set email alerts
|

Three J-proteins impact Hsp104-mediated variant-specific prion elimination: a new critical role for a low-complexity domain

Abstract: Prions are self-propagating protein isoforms that are typically amyloid. In Saccharomyces cerevisiae, amyloid prion aggregates are fragmented by a trio involving three classes of chaperone proteins: Hsp40s, also known as J-proteins, Hsp70s, and Hsp104. Hsp104, the sole Hsp100-class disaggregase in yeast, along with the Hsp70 Ssa and the J-protein Sis1, is required for the propagation of all known amyloid yeast prions. However, when Hsp104 is ectopically overexpressed, only the prion [PSI + ] is efficiently eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 77 publications
(113 reference statements)
3
11
0
Order By: Relevance
“…A recent study from the late Stephan Jentsch lab [31] has demonstrated that the yeast Hsp70/Apj1 bi-chaperone pair, in cooperation with Hsp110, exclusively couples the dissolution of INQ to 26S proteasome-mediated degradation, independently of Hsp104 function [32]. The involvement of the Hsp40 co-chaperone in the proteasome-dependent disaggregation of transient-QC is in line with findings that established Hsp40 co-chaperones not only as Hsp70 activators but also as regulators of their binding specificity and functional diversity [32][33][34][35]. Now, the den Brave study, not only establishes the function of the nuclear Hsp40, Apj1, in INQ clearance, but it also indicates that Hsp104-dependent refolding and proteasome-mediated degradation of solubilized misfolded proteins are independent disaggregation triage reactions [32].…”
Section: Misfolded Proteins Are Extracted From Cell Inclusions and Sosupporting
confidence: 56%
“…A recent study from the late Stephan Jentsch lab [31] has demonstrated that the yeast Hsp70/Apj1 bi-chaperone pair, in cooperation with Hsp110, exclusively couples the dissolution of INQ to 26S proteasome-mediated degradation, independently of Hsp104 function [32]. The involvement of the Hsp40 co-chaperone in the proteasome-dependent disaggregation of transient-QC is in line with findings that established Hsp40 co-chaperones not only as Hsp70 activators but also as regulators of their binding specificity and functional diversity [32][33][34][35]. Now, the den Brave study, not only establishes the function of the nuclear Hsp40, Apj1, in INQ clearance, but it also indicates that Hsp104-dependent refolding and proteasome-mediated degradation of solubilized misfolded proteins are independent disaggregation triage reactions [32].…”
Section: Misfolded Proteins Are Extracted From Cell Inclusions and Sosupporting
confidence: 56%
“…The Hsp104 is essential for all amyloid-based cytosolic yeast prions [18,23]. The machinery also includes members of the Hsp70 family Ssa [24,25,26,27] and cochaperones of the Hsp40 family, also known as J-proteins [28,29,30]. In the current model of [ PSI + ] prion propagation, the Hsp70/40 complex binds to amyloid fibrils and recruits Hsp104 [31].…”
Section: Yeast Prions and Protein Quality Controlmentioning
confidence: 99%
“…Among Hsp40s, Sis1p (the only essential Hsp40 [ 116 ]) is required by [PSI+], [URE3], [PIN+], and [SWI+] [ 94 , 117 , 118 ], while Swa2 is specifically required for [URE3] [ 97 ]. The specificity appears to reside in the TPR domain of Swa2.…”
Section: Chaperones and Prionsmentioning
confidence: 99%